MasteringTM Windowsa. XP Home Edition. - Hart-Davis, Guy (John Wiley & Sons, 2006)
Here's the insider knowledge you need to maximize Microsoft's powerful home operating system, whether you're moving straight to XP or upgrading from Windows 98 or Me. This encyclopedic guide delivers full coverage of every topic from installation and multimedia, to security and networking. Beginners can start off by using Windows XP on a stand-alone computer and connecting to the Internet, while experienced users can quickly build and secure a home network, work with the Registry to change XP's behavior, and optimize and troubleshoot Windows XP.